2010
DOI: 10.1038/gt.2010.142
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral delivery of Tousled kinase for the protection of salivary glands against ionizing radiation damage

Abstract: Oral complications of salivary hypofunction often afflict cancer patients undergoing radiotherapy for head and neck cancers. Dry mouth or xerostomia is an undesirable consequence of radiotherapy that compromises normal oral functions in addition to causing odynophagia and increasing the patient's risk of oral infections and dental caries. Radiation-induced xerostomia is irreversible, and palliative measures to provide symptomatic relief remain the mainstay of treatment. Previously, we identified a splice varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 50 publications
0
33
0
1
Order By: Relevance
“…We have shown that expression of TLK1B in mouse epithelial cells does not induce oncogenic transformation, but it does increase the cell's ability to overcome radiation injury (Li et al, 2001;SunavalaDossabhoy et al, 2003;Sunavala-Dossabhoy et al, 2005). This holds true for irradiated normal rat salivary acinar and ductal cells transduced with exogenous TLK1B as well (Palaniyandi et al, 2011;Sunavala-Dossabhoy et al, 2012). Although TLK1B facilitates repair of double-strand breaks, its precise role in this process is not completely elucidated.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…We have shown that expression of TLK1B in mouse epithelial cells does not induce oncogenic transformation, but it does increase the cell's ability to overcome radiation injury (Li et al, 2001;SunavalaDossabhoy et al, 2003;Sunavala-Dossabhoy et al, 2005). This holds true for irradiated normal rat salivary acinar and ductal cells transduced with exogenous TLK1B as well (Palaniyandi et al, 2011;Sunavala-Dossabhoy et al, 2012). Although TLK1B facilitates repair of double-strand breaks, its precise role in this process is not completely elucidated.…”
Section: Introductionmentioning
confidence: 90%
“…Previously, we had shown that a single-dose of 16 Gy compromises rat submandibular gland function, and pretreatment with adenovirus-TLK1B effectively salvaged salivary flow (Palaniyandi et al, 2011). To assess the effect of TLK1B on clinically relevant radiation dosing, animals were irradiated in fractions of 2.5 Gy daily, up to a total of 20 Gy (Fig.…”
Section: Tlk1b Ameliorates Fractionated Radiation-induced Hyposalivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, for viral-mediated gene therapy in humans, the SGs offer several advantages with respect to other organs: i) the encapsulation of the SG tissue prevents the dissemination of the virus in the rest of the body (Baum et al, 2004;Voutetakis et al, 2004), ii) in case of potential health issues the SGs can be removed since they are not essential for life, iii) the differentiation of the cells provides a relatively stable cell populations for non-integrating vectors, and iv) duacrine (both exocrine and endocrine) protein secretion allows to direct the expressed molecules into either the saliva or the blood stream (Baum et al, 2004). Numerous studies have shown successful gene transfer into both rat and mouse submandibular glands using viral-based approaches, which offer the advantage of a more robust expression of the transgenes (Andresen et al, 2009;Baum and Tran, 2006;Delporte et al, 1996;Honigman et al, 2001;Mastrangeli et al, 1994;Morita et al, 2011;Palaniyandi et al, 2011;Perez et al, 2011;Samuni et al, 2008;Wang et al, 2000;Zheng et al, 2009). However, non viral-mediated approaches have also been utilized, although limited to a small percentage of the cells in the parenchyma (Goldfine et al, 1997;Honigman et al, 2001;Niedzinski et al, 2003a;Niedzinski et al, 2003b;Passineau et al, 2010;Sramkova et al, 2009).…”
Section: Delivery Of Molecules Drugs and Gene Transduction In The Samentioning
confidence: 99%